Functional outcomes among stroke patients in Alagoas, Brazil: observational study - Baggio,Jussara Almeida de Oliveira (2021)
ABSTRACT BACKGROUND: Stroke is the principal cause of disability around the world and the ensuing functional dependence (FD) can be correlated with different factors. OBJECTIVE: To determine how demographic factors and clinical characteristics after stroke distinguish patients who achieve functional independence from those who do not. DESIGN AND SETTING: Observational study at specialized neurovascular clinic in Alagoas, Brazil. METHODS: FD was classified according to the modified Rankin scale (mRs): 0 to 2 points were classified as independent (FD-), and 3 to 5 points were classified as dependent (FD+). Logistic regression analysis included age, sedentary lifestyle, the Center for Epidemiological Studies – Depression Scale (CES-D) and the National Institutes of Health Stroke Scale (NIHSS). The Mann-Whitney test and χ2 test were used to compare groups. RESULTS: We included 190 stroke patients with a mean age of 60.02 ± 14.22 years. We found that 34.8% of the patients were classified as FD+. Lower NIHSS and CES-D scores were more associated with achieving functional independence. Most of the patients had access to physical therapy, and the mean duration of rehabilitation therapy was 65.2 minutes per week. Females had higher prevalence of depressive symptoms (P = 0.005) and rehabilitation time was shorter for hemorrhagic stroke (P = 0.02). CONCLUSION: We found a FD rate four times greater than in another Brazilian study. Lower stroke severity and fewer depressive symptoms were associated with achieving functional independence. Less than half of the patients were referred to a rehabilitation service at hospital discharge and few had access to multidisciplinary treatment.